Penguatan Pariwisata Pesisir Berkelanjutan melalui Aksi Lingkungan Kolaboratif di Pantai Pancer, Jember - Firda Diartika; Enik Rukiati; Muhammad Dzulkifli; Tri Rafika Diyah Indartin; Hablana Rizka (Yayasan Literasi Sains Indonesia, 2026)
Pancer Beach, located in Jember Regency, represents a significant coastal destination endowed with vast ecological and economic potential; however, it currently faces deleterious environmental challenges due to substantial waste accumulation. This community service initiative was designed to revitalise the environmental quality of the area, cultivate ecological consciousness among the local populace, and fortify multi-stakeholder engagement in the management of sustainable tourism. The methodology employed a systematic framework encompassing strategic coordination, direct environmental interventions, and participatory evaluation, further substantiated by pre-test and post-test measurements to quantify the project's impact. The primary activities involved the restoration of coastal vegetation through the planting of sea pines (Casuarina equisetifolia) and Tabebuia trees, alongside a collaborative beach clean-up campaign. Involving approximately 150 participants, this collective effort successfully mitigated environmental hazards by collecting between 300 and 400 kg of refuse. The results indicate a marked improvement in the aesthetic and ecological integrity of the tourist zone, complemented by a significant shift in community perception. This was evidenced by an increase in average comprehension scores from 68 to 92, while environmental awareness levels escalated from 65% to 80%. Furthermore, the initiative successfully fostered institutional synergy among various stakeholders. Ultimately, this project demonstrates that a collaborative, action-oriented approach is highly efficacious in accelerating the development of sustainable maritime tourism.